Thrombotic risk factors in Chinese Budd-Chiari syndrome patients - Qi, Xingshun; Wu, Feifei; Ren, Weirong; He, Chuangye; Yin, Zhanxin; Niu, Jing; Bai, Ming; Yang, Zhiping; Wu, Kaichun; Fan, Daiming; Han, Guohong (Thrombosis and Haemostasis, 2013)
In Western countries, thrombotic risk factors for Budd-Chiari syndrome (BCS) are very common, including factor V Leiden mutation, prothrombin G20210A mutation, myeloproliferative neoplasms, paroxysmal nocturnal haemoglobinuria, etc. However, the data regarding thrombotic risk factors in Chinese BCS patients are extremely limited. An observational study was conducted to examine this issue. A total of 246 BCS patients who were consecutively admitted to our department between July 1999 and December 2011 were invited to be examined for thrombotic risk factors. Of these, 169 patients were enrolled. Neither factor V Leiden mutation nor prothrombin G20210A mutation was found in any of 136 patients tested. JAK2 V617F mutation was positive in four of 169 patients tested. Neither MPL W515L/K mutation nor JAK2 exon 12 mutation was found in any of 135 patients tested. Overt myeloproliferative neoplasms were diagnosed in five patients (polycythemia vera, n=3; essential thrombocythemia, n=1; idiopathic myelofibrosis, n=1). Two of them had positive JAK2 V617F mutation. Both CD55 and CD59 deficiencies were found in one of 166 patients tested. This patient had a previous history of paroxysmal nocturnal haemoglobinuria before BCS. Anticardiolipin IgG antibodies were positive or weakly positive in six of 166 patients tested. Hyperhomocysteinaemia was found in 64 of 128 patients tested. 5,10-methylenetetrahydrofolate reductase C677T mutation was found in 96 of 135 patients tested. In conclusion, factor V Leiden mutation, prothrombin G20210A mutation, myeloproliferative neoplasms, and paroxysmal nocturnal haemoglobinuria are very rare in Chinese BCS patients, suggesting that the etiological distribution of BCS might be different between Western countries and China.
Keywords: Budd-Chiari syndrome; factor V Leiden mutation; prothrombin G20210A mutation; myeloproliferative neoplasm; paroxysmal nocturnal haemoglobinuria